New insights into phenotype and genotype relationships in Neospora caninum - Cabrera, Andres; Berná, Luisa; López, Lucía; Faral-Tello, Paula; Arevalo, Ana Paula; Crispo, Martina; Francia, Maria E.; Robello, Carlos (Frontiers in Veterinary Science, 2023)
The successful isolation of four new Neospora caninum strains from different regions and with different backgrounds (obtained from an abortion storm or congenitally infected and asymptomatic calves) allowed us previously to characterize natural isolates, finding differences in phenotype and microsatellites. Given the variability observed, we wondered in this work whether these differences had consequences in virulence, invasion and vertical transmission using cell cultures and murine neosporosis models. In addition, we performed the genomic analysis and SNP comparative studies of the NcURU isolates. The results obtained in this work allowed us to establish that NcURU isolates are of low virulence and have unique phenotypic characteristics. Likewise, sequencing their genomes has allowed us to delve into the genetic singularities underlying these phenotypes, as well as the common mutated genes. This work opens a new perspective for diagnostic purposes and formulating possible vaccines based on attenuated strains.